International issues of the day are general for the whole world (Herald of Journalism, 2018)
In MASS-MEDIA his writing and ways of decision is important not only for one nation but also the world. Presently experience of foreign mass medias it is important and for Kazakhstan. This article was deeper in analyzing leading publications, television news and writing. Many examples were carried out.
Keywords: Key words: International journalism, description, world Media, actual problems.